An educational virtual lab to study a mixed gearing of wheels - Montenegro Joo, Javier (2010)
An educational Virtual Lab dealing with a mixed gearing of wheels has been created. Gears of wheels are common in Mechanical Engineering applications, like industrial machinery. This Virtual Lab is ideal when teaching and/or learning the relationship between geared wheels having three types of contact: tangent, coaxial, and by a belt. The virtual lab performs simulation based on the mathematical modeling of the gearing and allows the user to visualize the behavior of a mixed gearing of wheels and to get acquainted with the rotation speeds, number of turns and other parameters that appear when a set of wheels are geared